Comprehensive Impacts of Climate Change on Rice Production and Adaptive Strategies in China - Saud, Shah; Wang, Depeng; Fahad, Shah; Alharby, Hesham F.; Bamagoos, Atif A.; Mjrashi, Ali; Alabdallah, Nadiyah M.; AlZahrani, Saleha S.; AbdElgawad, Hamada; Adnan, Muhammad; Sayyed, R. Z.; Ali, Shafaqat; et al. (Frontiers in Microbiology, 2022)
Rice production system is one of the most sensitive agro-ecosystems to climate change. This paper reviews the effects of current and future climate change on rice production in China. Under the background of climate change, heat resources increased, radiation resources decreased, and precipitation heterogeneity increased in rice growing season in China. High temperature and heat disasters, droughts, heavy rains and floods occur more frequently, which may reduce the efficiency of water and heat resources. The potential planting boundary of single and double cropping rice in China has moved northward significantly due to climate change, leading to the shortening of the main growth period of single cropping rice, early cropping rice and late cropping rice. The results, based on statistical models and rice growth models, showed that climate change reduced yields of single-cropping, early and late rice, regardless of advances in variety improvement and cultivation techniques, but there were differences among different rice growing areas and methods. The trend of the center of gravity of rice production moving northward, the measured extension of growth period and the increase of yield in China reflects the ability of rice production system to adapt to climate change through planting distribution adjustment, variety improvement and technological improvement. In the future, climate change will further shorten the growth period and decrease rice yield, which will bring severe challenges to rice production and food security in China. It is still necessary to strengthen the research on the impact mechanism of climate change and its application in impact assessment, reduce the uncertainty of impact assessment and increase its systematicness, and provide reliable theoretical support for the formulation of effective coping strategies